LIFE CYCLE COST OF DRUM DISPLACER -WASHER - Kurvinen, Matti (My University, 2018)
In order to determine the total costs of new investments as well as already existing systems one must always take into consideration the life cycle costs. Due to lack of research investments can be significantly more expensive in the long run than expected. It is becoming more and more important to also minimize life cycle costs as companies are compelled to be more cost efficient in every area of operation. The aim of this research was to calculate and determine ways to minimize Drum Displacer –washer’s life cycle costs. The study was conducted in cooperation with Andritz Oy. The focus of this research was on the main machine of fiber line production, DD-4070 washer. The results of this study will have a notable impact in the sales of spare parts, whole fiber lines and rebuilding. Furthermore, the conclusions can be utilized in the life cycle calculations of the case company. The materials used in this research were relevant literature, documents and the Internet. The research methods used were secondary research on previous studies and expert interviews. In the expert interviews, that supplemented the written sources, people working with life cycle costs were consulted. The theoretical part of the research was formed by the case company’s life cycle cost and criticality analysis. The specialist interviews complemented the theoretical part and determined how the case company’s life cycle costs were performed. The main focus of the interviews was to figure out how the life cycle cost calculation is formulated and performed in DD-washers. There were differences found in the ways of calculating the life cycle costs between the case company’s various product groups. These differences cause divergent cost estimates in the final results. A simple and efficient method to minimize the life cycle costs and estimate the criticality of spare part change was determined as a result of the study. The minimization of costs requires a great effort throughout the production line but the savings from it ensue during the whole life cycle. Additionally, in order to minimize more costs it is important to increase the cooperation between the case company and its customers. According to the interviews and literature the greatest saving opportunities lie in the planning and implementation of maintenance and in the sales of spare part packages.
Keywords: Life cycle; life-cycle cost; costing model; criticality analysis; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|